Larvicidal, Ovicidal, Synergistic, and Repellent Activities of Sophora alopecuroides and Its Dominant Constituents Against Aedes albopictus - Rana Fartab Shoukat; Muhammad Shakeel; Syed Arif Hussain Rizvi; Junaid Zafar; Yuxin Zhang; Shoaib Freed; Xiaoxia Xu; Fengliang Jin (Insects, 2020)
In the current study, to combat insecticide resistance, we explored larvicidal, ovicidal, synergistic, and repellent activities of Sophora alopecuroides extract and its dominant constituents against Aedes albopictus. The results of the toxicity bioassays demonstrated that the extract of S. alopecuroides exerted significant larvicidal activity (16.66–86.66%) against the third-instar larvae of Ae. albopictus at different concentrations (5–50 ug/mL) and low hatchability of eggs (2.32–75%) at 5–50 ug/mL. The constituents of S. alopecuroides showed a synergistic effect when applied as a mixture (LC30 + LC30) against larvae, while no synergistic effect was observed against the eggs of Ae. albopictus. S. alopecuroides extract provided 93.11% repellency in the first 90 min and gradually decreased to 53.14% after 240 min, while the positive control DEET (N,N-diethyl-3-methylbenzamide) showed 94.18% in the first 90 min and 55.33% after 240 min. All of the results exhibited a concentration-dependent effect. To the best of our knowledge, this is the first time that a study has identified a highly effective extract of S. alopecuroides, which could be used as an alternative agent to control larvae and eggs and to repel adults of Ae. albopictus.